Attenuation of TNF-α-Induced Inflammatory Injury in Endothelial Cells by Ginsenoside Rb1 via Inhibiting NF-κB, JNK and p38 Signaling Pathways - Zhou, Ping; Lu, Shan; Luo, Yun; Wang, Shan; Yang, Ke; Zhai, Yadong; Sun, Guibo; Sun, Xiaobo (Frontiers in Pharmacology, 2017)
It is currently believed that inflammation plays a central role in the pathophysiology of atherosclerosis (AS). Oxidative stress and redox-sensitive transcription factors are implicated in the process. Ginsenoside Rb1, a major active ingredient in processed Radix notoginseng, has attracted widespread attention because of its potential to improve cardiovascular function. However, the effects of ginsenoside Rb1 on tumor necrosis factor α (TNF-α)-induced vascular endothelial cell injury and the underlying molecular mechanisms have never been studied. This study showed that TNF-α-induced oxidative stress, inflammation and apoptosis in human umbilical vein endothelial cells (HUVECs) could be attenuated by ginsenoside Rb1 pretreatment. Using JC-1, Annexin V/PI and TUNEL staining, and a caspase-3 activity assay, we found that Rb1 provided significant protection against TNF-α-induced cell death. Furthermore, Rb1 pretreatment could inhibit TNF-α-induced ROS and MDA production; increase the activities of SOD, CAT and GSH-Px; and decrease the levels of IL-1β, IL-6, VCAM-1, ICAM-1, VEGF, MMP-2 and MMP-9. Importantly, the cytoprotective effects of Rb1 were correlated with NF-κB signaling pathway inhibition. Additionally, we found that Rb1 may suppress the NF-κB pathway through p-38 and JNK pathway activation, findings supported by the results of our experiments involving anisomycin (AM), a JNK and p38 activator. In conclusion, this study showed that ginsenoside Rb1 protects HUVECs from TNF-α-induced oxidative stress and inflammation by inhibiting JNK and p38. This inhibition suppressed NF-κB signaling and down-regulated the expression of inflammatory factors and apoptosis-related proteins.